Antimicrobial resistance and virulence gene profiles of Escherichia coli isolated from poultry farms using One Health perspective in Abeokuta, Nigeria - A. T. Ajibola; M. de Lagarde; O. E. Ojo; S. A. Balogun; G. Vanier; J. M. Fairbrother; O. B. Shittu (BMC Microbiology)
Abstract Background Antimicrobial resistant Extraintestinal pathogenic Escherichia coli (ExPEC) includes uropathogenic E. coli (UPEC), the causative agents of urinary tract infections (UTI), neonatal meningitis E. coli (NMEC), implicated in neonatal meningitis in humans, and avian pathogenic E. coli (APEC). Antimicrobial resistant ExPEC infections are associated with economic losses in poultry worldwide. However, few studies have been done on ExPEC in Nigeria. Methods In order to gain further insight into the presence of antimicrobial resistant ExPEC in poultry and the putative transmission of E. coli isolates from healthy chickens to poultry owners and/or the environment, antimicrobial susceptibility testing (AST) and polymerase chain reaction (PCR) to determine the presence of 5 virulence genes considered as ExPEC predictors were carried out on 71 E. coli isolates from apparently healthy chickens, their handlers and their shared environment, in Abeokuta, Ogun State, Nigeria. In addition, 14 of the 71 isolates were characterized using whole genome sequencing. Results Regardless of the source, 70.4% of the isolates were multidrug-resistant (MDR) and 66.2% of the isolates were resistant to fluoroquinolones. Only 3 out of the 71 isolates had at least 2 ExPEC predictor genes and the proportion of antimicrobial resistance (AMR) was higher in isolates with at least 1 ExPEC predictor gene. Thirty different resistance determinants were identified from the 14 whole genome sequenced isolates and most of the sequenced isolates harbored plasmid-mediated resistance genes, including aph(3″)-Ib, aph(6)-Id, floR, sul1, sul2, tet(A), and tet(B). Isolates were very diverse, 11 different serotypes and 12 different sequence types being detected in this study. Twenty different replicons were also found, IncF1B being the most frequently detected. Different ExPEC virulent genes and virulence associated genes (VAGs) for iron acquisition, toxin production, invasion and other virulence determinants were detected. Conclusions Our results suggest that apparently healthy birds carry antimicrobial resistant genes and virulence genes, underlining their possible transmission to humans. The presence of similar ARGs and VAGs in the handlers of birds and their shared environment highlights the importance of using a One Health approach.